PENEGAKAN HUKUM TINDAK PIDANA PERDAGANGAN ORANG PEKERJA MIGRAN INDONESIA - Dewi Asri Puanandini (Fakultas Syariah dan Hukum UIN Sunan Gunung Djati Bandung, 2020)
This study aims to examine the problems of law enforcement against human trafficking against Indonesian migrant workers. This research was conducted on legal issues from the normative side based on the rule of law in legislation and norms. This study uses a normative juridical approach with primary and secondary legal materials. The results of this study indicate that the law enforcement process against the criminal act of trafficking of Indonesian migrant workers, there are parties that are organized, starting from the Indonesian Migrant Worker Placement Company for Civil Employment, Health (medical checkup), Immigration (making passports), and at the airport. P3MI uses unscrupulous immigration officers who can pass prospective Indonesian migrant workers with a number of rewards. Law enforcement carried out by the Indonesian Migrant Workers Protection Agency by postponing services, revoking company permits, written warnings, temporarily suspending part or all of business activities, canceling the departure of prospective migrant workers, and or returning from abroad at their own expense. The long-term effort is to closely monitor Indonesian labor service companies.